Antimony-doped iridium oxide catalyst and preparation method and oxygen evolution application thereof
By introducing antimony elements into IrOx and loading them on Sb0.2Sn0.8O2 support, a high-activity and stable SbmIr1-mOx@TB-IrOx/Sb0.2Sn0.8O2 nanocatalyst was prepared, which solved the problems of poor stability and high Ir rarity of PEM electrolytic cell, and achieved high efficiency and low-cost catalytic performance.
Patent Information
- Application Number
- CN202411712254.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
Smart Images

Figure CN119530875A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of acidic water electrolysis catalysts, and in particular relates to an antimony element-doped iridium oxide catalyst and a preparation method and oxygen evolution application thereof. Background Art
[0002] The long-term use of traditional fossil fuels (such as oil, coal, natural gas, etc.) has caused serious environmental pollution and brought about problems such as global warming. Compared with fossil energy, hydrogen energy is an efficient and environmentally friendly secondary energy. It is recognized as a very promising energy carrier due to its high energy density, and is therefore hailed as the ultimate energy of the 21st century. There are many process routes for hydrogen production. Among them, the cost of hydrogen production from fossil energy (coal, natural gas, etc.) is low, but the purity of the obtained hydrogen is low and it is often accompanied by the production of carbon dioxide, which is contrary to the "dual carbon" policy. In addition, waste gas and waste liquid are still generated during its reproduction process, resulting in environmental pollution. Compared with the former "gray hydrogen" production process, the electrolysis of water hydrogen production technology currently uses electricity to directly decompose water into H2 and O2. Its energy can be provided by intermittent green energy (such as solar energy, wind energy, tidal energy, etc.), avoiding the use of fossil energy and greenhouse gas emissions throughout the process. Proton exchange membrane water electrolysis (PEMWE) is an effective method for preparing green hydrogen. However, since water electrolysis involves an oxygen evolution reaction with four electron transfer, it has an excessively high potential, which becomes a huge obstacle to the development of PEMWE. In addition, the working environment of the PEMWE anode is highly acidic and oxidizing, which in turn poses a great challenge to the stability of the OER catalyst. Therefore, the development of efficient and stable OER catalysts is conducive to achieving high water electrolysis efficiency in PEM electrolyzers, thereby promoting their large-scale commercial application. At present, IrO2 is the catalyst with the best acidic OER activity and stability. Nevertheless, as one of the most scarce elements, Ir's expensive price and scarce output have always restricted its large-scale application. Therefore, how to rationally design Ir-based catalysts and reduce their dosage as much as possible while improving catalytic activity is the key to the development of PEMWE. Summary of the invention
[0003] The present invention aims to develop high-quality, active, and stable Ir-based catalysts for use in the field of OER in PEM electrolyzers. x The invention provides an antimony-doped iridium oxide catalyst and its preparation method and oxygen evolution application by doping with stable metal elements and loading on a metal oxide carrier. The preparation method of the invention is novel, and the obtained catalyst has high acidic OER activity and stability.
[0004] To achieve the above object, the present invention adopts the following technical solution:
[0005] In a first aspect, a method for preparing an antimony-doped iridium oxide catalyst comprises the following steps:
[0006] (1) Synthesis of Sb-doped SnO2 carrier powder: SnCl2·2H2O, citric acid and SbCl3 are dissolved in ethanol solution, then heated in a water bath and the pH of the mixed solution is adjusted to 5-7; then evaporated to obtain a white powder, which is then calcined in a muffle furnace, and then the obtained powder is washed, filtered and dried to obtain a blue powder, i.e., Sb 0.2 Sn 0.8 O2;
[0007] (2) Synthesis of Sb m Ir 1-m O x @TB-IrO x / Sb 0.2 Sn 0.8 O2 nanocatalyst precursor: First, Sb 0.2 Sn 0.8 O2 and IrCl3 powders are placed in ethanol and ultrasonicated; then citric acid and SbCl3 are added and ultrasonicated again. Finally, the pH of the solution is adjusted to neutral; the resulting solution is dried into powder, and the precursor preparation is completed;
[0008] (3) placing the precursor in a muffle furnace and calcining to obtain a black powder; washing the black powder several times to obtain Sb m Ir 1-m O x @TB-IrO x / Sb 0.2 Sn 0.8 O2 nanocatalyst, that is, antimony-doped iridium oxide catalyst.
[0009] Furthermore, in the step (1), the molar ratio of citric acid to metal salt is 0.5-1.5:5-15; the metal salt is SbCl3 and SnCl2·2H2O, wherein the molar ratio of SbCl3 to SnCl2·2H2O is 1-4:6-9.
[0010] Furthermore, the water bath heating time is 20-40 minutes, and the water bath heating temperature is 50-70°C.
[0011] Furthermore, in step (1), the steps of washing, centrifuging and filtering the obtained powder are repeated 7 to 8 times.
[0012] Furthermore, in the step (2), the two ultrasonic times are 0.5-1 hour and 1-2 hours respectively.
[0013] Furthermore, in step (1), the pH of the mixed solution is adjusted by using a NaOH ethanol solution; the concentration of the NaOH ethanol solution is 1 mmol / mL.
[0014] Furthermore, in the step (1), the muffle furnace calcination condition is to heat to 500-600°C at 5°C / min, continue heating for 1-2 hours, and then naturally cool to room temperature.
[0015] Furthermore, in step (2), Sb 0.2 Sn 0.8 The molar ratio of O2, citric acid and metal salt is 0.5-1:0.5-1.5:5-15; the metal salt is SbCl3 and IrCl3, wherein the molar ratio of SbCl3 and IrCl3 is 0-4:6-10.
[0016] Furthermore, in step (1) and step (2), the drying temperature is 40-60°C.
[0017] Furthermore, in step (3), the muffle furnace calcination condition is to heat to 450-500°C at 10°C / min; the sample is heated continuously for 0.5-1 hour and then cooled naturally.
[0018] In a second aspect, the present invention also provides a Sb prepared according to the above preparation method. m Ir 1-m O x @TB-IrO x / Sb 0.2 Sn 0.8 O2 nanocatalyst.
[0019] In a third aspect, the present invention also provides a Sb m Ir 1-m O x @TB-IrO x / Sb 0.2 Sn 0.8 Application of O2 nanocatalysts in acidic oxygen evolution reaction.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The present invention is directed to IrO x The Sb element was introduced into the catalyst, and a nanocatalyst rich in twin boundaries and with a core-shell structure was prepared by rapid pyrolysis, achieving the coordinated regulation of the catalyst electronic structure by strain caused by doping and twin boundaries. The synergistic effect of strain caused by twin boundaries and metal doping regulates the movement of the Ir 5d band center (εd) toward the Fermi level, thereby enhancing the adsorption capacity of active sites for oxygen intermediates and improving the catalyst activity and stability.
[0022] (2) Sb-doped IrO x Nanoparticles loaded on Sb 0.2 Sn 0.8On O2, a supported catalyst with doping and strain coordination effect was prepared, and a method for effectively coupling the synergistic effect of doping and strain with the load was proposed. Since the active particles on the carrier have a smaller particle size, the catalyst has a higher electrochemical active area, which improves the electrochemical reaction rate.
[0023] (3) Dispersing the active catalyst on the conductive material can effectively reduce the loading amount of the PEM anode catalyst, thereby reducing the cost of the PEM electrolyzer and promoting the commercial application and promotion of PEM. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative labor.
[0025] Figure 1 Synthesis of Sb for Example 1 0.3 Ir 0.7 O x @TB-IrO x / Sb 0.2 Sn 0.8 O2 flow chart and TEM image and EDS element distribution map of the sample prepared in Example 1;
[0026] Figure 2 Transmission electron microscope image and EDS element distribution map of the sample prepared in Comparative Example 2;
[0027] Figure 3 X-ray diffraction patterns of samples prepared in Example 1, Comparative Example 2 and Comparative Example 3;
[0028] Figure 4 X-ray photoelectron spectra of samples prepared in Example 1 and Comparative Examples 1-3;
[0029] Figure 5 Electrochemical test diagrams of samples prepared from Example 1, Comparative Examples 1-3 and commercial IrO2;
[0030] Figure 6 The density of states of Example 1 and Comparative Examples 1-3, the volcano-shaped relationship between the overpotential of the catalyst and the d-band center, and the ΔG of the catalyst are shown in FIG. *OOH -ΔG *OH volcano-type relationship with overpotential;
[0031] Figure 7 For Comparative Example 1 and Comparative Example 3TB-IrO x and Sb0.3 Ir 0.7 O x @TB-IrO x Modeling of the acidic OER and the free energies of the OER reaction steps at U = 0 V;
[0032] Figure 8 For Comparative Example 1 and Comparative Example 3TB-IrO x -2% and Sb 0.3 Ir 0.7 O x @TB-IrO x -2% acidic OER model and free energies of OER reaction steps at U = 0 V
[0033] Fig. 9 For comparative example 3TB-IrO x Modeling of acidic OER at different strains (1%, 4%, 6%, 8%) and free energies of acidic OER reaction steps at U = 0 V;
[0034] Fig.10 For comparative example 1Sb 0.3 Ir 0.7 O x @TB-IrO x Modeling of acidic OER at different strains (1%, 4%, 6%, 8%) and free energies of acidic OER reaction steps at U = 0 V;
[0035] Fig.11 The DOS electronic structure of comparative example 3 under different strain adjustments;
[0036] Fig.12 The DOS electronic structure of Comparative Example 1 under different strain adjustments;
[0037] Fig.13 Schematic diagram of a proton exchange membrane (PEM) electrolyzer (MEA: membrane electrode assembly; CP: carbon paper; Pt@Ti: platinum-coated titanium felt; GDL: gas diffusion layer), polarization curves and TOF of the samples prepared in Example 1, Comparative Examples 1 and 2 as anode catalysts of the PEM electrolyzer, and the TOF of the sample prepared in Example 1 at 2 A cm -2 Chronopotentiometry curve of the PEM electrolyzer operating under
[0038] Fig.14 Transmission electron microscope image and EDS element distribution map of the sample prepared in Example 1 after OER reaction;
[0039] Fig.15 This is the X-ray diffraction pattern of the sample prepared in Example 1 after OER reaction;
[0040] Fig.16 This is the X-ray photoelectron spectrum of the sample prepared in Example 1 after OER reaction. DETAILED DESCRIPTION
[0041] The present invention is described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the features of the following embodiments and implementations can be combined with each other.
[0042] A novel antimony-doped iridium oxide catalyst and a preparation method thereof of the present invention comprises the following steps:
[0043] (1) Synthesis of Sb-doped SnO2 carrier powder: SnCl2·2H2O, citric acid and SbCl3 are dissolved in ethanol solution, then heated in a water bath and the pH of the mixed solution is adjusted to 5-7; then evaporated to obtain a white powder, which is then calcined in a muffle furnace, and then the obtained powder is washed, filtered and dried to obtain a blue powder, i.e., Sb 0.2 Sn 0.8 O2;
[0044] (2) Synthesis of Sb m Ir 1-m O x @TB-IrO x / Sb 0.2 Sn 0.8 O2 nanocatalyst precursor: First, Sb 0.2 Sn 0.8 O2 and IrCl3 powders are placed in ethanol and ultrasonicated; then citric acid and SbCl3 are added and ultrasonicated again. Finally, the pH of the solution is adjusted to neutral; the resulting solution is dried into powder, and the precursor preparation is completed;
[0045] (3) placing the precursor in a muffle furnace and calcining to obtain a black powder; washing the black powder several times to obtain Sb m Ir 1-m O x @TB-IrO x / Sb 0.2 Sn 0.8 The O2 nanocatalyst is an antimony-doped iridium oxide catalyst, wherein the value of m is determined according to the molar ratio of SbCl3 to IrCl3 in step (2).
[0046] In one embodiment, in the step (1), the molar ratio of citric acid to metal salt is 0.5-1.5:5-15, such as 1:10, 1:15, 3:10, etc., which are not listed here; the metal salt is SbCl3 and SnCl2·2H2O, wherein the molar ratio of SbCl3 and SnCl2·2H2O is 1-4:6-9, such as 1:6, 1:9, 4:6, etc., which are not listed here, but the added amount is not 0.
[0047] In one embodiment, in step (1), the water bath heating time can be any value in the range of 20-40 minutes, such as 20 minutes, 30 minutes, 40 minutes, etc., which are not listed here in detail; the water bath heating temperature can be any value in the range of 50-70°C, such as 50°C, 60°C, 70°C, etc., which are not listed here in detail.
[0048] In one embodiment, in step (1), the steps of washing, centrifuging and filtering the obtained powder are repeated 7 to 8 times.
[0049] In one embodiment, in step (2), the two ultrasonic times are 0.5-1 hour and 1-2 hours respectively.
[0050] In one embodiment, in step (1), the pH of the mixed solution is adjusted by using a NaOH ethanol solution; preferably, the concentration of the NaOH ethanol solution is 1 mmol / mL.
[0051] In one embodiment, in step (1), the muffle furnace calcination condition is to heat to 500-600° C. at 5° C. / min, continue heating for 1-2 hours, and then naturally cool to room temperature.
[0052] In one embodiment, in step (2), Sb 0.2 Sn 0.8 The molar ratio of O2, citric acid and metal salt is 0.5-1:0.5-1.5:5-15, such as 0.5:0.5:5, 0.5:0.5:15, 0.5:1.5:5, 0.5:1.5:15, 1:0.5:5, 1:0.5:15, 1:1.5:5, 1:1.5:15, 0.7:1:10, 1:1:15, 0.5:1:10 and so on, which are not listed here in detail; the metal salt is SbCl3 and IrCl3, wherein the molar ratio of SbCl3 and IrCl3 is 0-4:6-10, and the amount of SbCl3 added can be 0.
[0053] In one embodiment, in step (1) and step (2), the drying temperature is any value between 40-60°C.
[0054] In one embodiment, in step (3), the muffle furnace calcination condition is to heat to any value between 450°C and 500°C at 10°C / min; the sample is heated continuously for 0.5-1 hour and then cooled naturally.
[0055] It should be noted that in other embodiments of the present invention, other different schemes obtained by making specific selections within the scope of the steps, components, ratios, and process parameters recorded in the present invention can all achieve the technical effects recorded in the present invention, so the present invention will no longer list them one by one.
[0056] The present invention uses Sb-doped SnO2 as a carrier and provides a rapid pyrolysis method to dope IrO with element Sb. x The formed nanoparticles rich in twin boundaries and with a core-shell structure are loaded on Sb-doped SnO2 carrier.
[0057] Embodiment 1:
[0058] (1) Dissolve 8mmol SnCl2·2H2O in 20ml ethanol, then add 1mmol citric acid and stir for 1h to make the solution uniform. Then, slowly add 2mmol SbCl3 while stirring and continue stirring for 1h. Seal the above solution and place it in a 60℃ water bath and keep heating for 30min. Then, in a 60℃ water bath, continue stirring and slowly add 1mmol / mL NaOH ethanol solution until the pH of the solution reaches 5 to obtain a milky white sol. Place the above sol in a 60℃ water bath to evaporate, while keeping the solution stirred. Place the white powder obtained after evaporation in a muffle furnace, set the temperature to 5℃ / min, heat to 500℃, continue heating for 1h, and then naturally cool to room temperature. Place the obtained powder in deionized water and ultrasonicate for 1h until the powder is completely dispersed in the water, then centrifuge, filter, and dry. Repeat the washing, centrifugation, and filtration steps 7-8 times. Finally, a blue Sb 0.2 Sn 0.8 O2 powder;
[0059] (2) 7 mmol of Sb 0.2 Sn 0.8 O2、7mmol IrC l3 The powder was placed in 30 mol of ethanol and ultrasonicated for 1 h. Then 0.1 mmol of citric acid and 3 mmol of SbCl3 were added respectively and ultrasonicated for 2 h. Finally, the pH of the solution was adjusted to 7. The resulting solution was dried into powder, and Sb 0.3 Ir 0.7 O x @TB-IrO x / Sb 0.2 Sn 0.8 The O2 precursor is prepared;
[0060] (3) Place the above precursor in a muffle furnace and quickly heat it to 450°C. Keep heating the drug for 30 minutes, then cool it down naturally to obtain a black powder. Wash the powder several times to obtain Sb 0.3 Ir 0.7 O x @TB-IrO x / Sb 0.2 Sn 0.8 O2 nanocatalyst.
[0061] Comparative Example 1:
[0062] (1) 7 mmol IrC l3 The powder was placed in 30 mol of ethanol and ultrasonicated for 1 h. Then 0.1 mmol of citric acid and 3 mmol of SbCl3 were added respectively and ultrasonicated for 2 h. Finally, the pH of the solution was adjusted to 7. The resulting solution was dried into powder, and Sb 0.3 Ir 0.7 O x @TB-IrO x The precursor preparation is completed;
[0063] (3) Place the above precursor in a muffle furnace and quickly heat it to 450°C. Keep heating the drug for 30 minutes, then cool it down naturally to obtain a black powder. Wash the powder several times to obtain Sb 0.3 Ir 0.7 O x @TB-IrO x Nanocatalyst.
[0064] Comparative Example 2:
[0065] (1) Dissolve 8mmol SnCl2·2H2O in 20ml ethanol, then add 1mmol citric acid and stir for 1h to make the solution uniform. Then, slowly add 2mmol SbCl3 while stirring and continue stirring for 1h. Seal the above solution and place it in a 60℃ water bath and keep heating for 30min. Then, in a 60℃ water bath, continue stirring and slowly add 1mmol / mL NaOH ethanol solution until the pH of the solution reaches 5 to obtain a milky white sol. Place the above sol in a 60℃ water bath to evaporate, while keeping the solution stirred. Place the white powder obtained after evaporation in a muffle furnace, set the temperature to 5℃ / min, heat to 500℃, continue heating for 1h, and then naturally cool to room temperature. Place the obtained powder in deionized water and ultrasonicate for 1h until the powder is completely dispersed in the water, then centrifuge, filter and dry. Repeat the above steps 7-8 times. Finally, blue Sb 0.2 Sn 0.8 O2 powder;
[0066] (2) 7 mmol of Sb0.2 Sn 0.8 O2, 10mmol IrC l3 The powder was placed in 30 mol of ethanol and ultrasonicated for 1 h. Then 0.1 mmol of citric acid was added and ultrasonicated for 2 h. Finally, the pH of the solution was adjusted to 7. The resulting solution was dried into powder, and TB-IrO x / Sb 0.2 Sn 0.8 The O2 precursor is prepared;
[0067] (3) Place the above precursor in a muffle furnace and quickly heat it to 450°C. Keep heating the drug for 30 minutes, then cool it down naturally to obtain a black powder. Wash the powder several times to obtain TB-IrO x / Sb 0.2 Sn 0.8 O2 nanocatalyst.
[0068] Comparative Example 3:
[0069] (2) 10 mmol IrC l3 The powder was placed in 30 mol of ethanol and ultrasonicated for 1 h. Then 0.1 mmol of citric acid was added and ultrasonicated for 2 h. Finally, the pH of the solution was adjusted to 7. The resulting solution was dried into powder, and TB-IrO x The precursor preparation is completed;
[0070] (3) Place the above precursor in a muffle furnace and quickly heat it to 450°C. Keep heating the drug for 30 minutes, then cool it down naturally to obtain a black powder. Wash the powder several times to obtain TB-IrO x Nanocatalyst.
[0071] Figure 1 Figure (a) shows the preparation of Sb in Example 1 0.3 Ir 0.7 O x @TB-IrO x / Sb 0.2 Sn 0.8 Preparation flow chart of O2. First, the metal oxide precursor is prepared by hydrothermal method, and then Sb is prepared by pyrolysis. 0.2 Sn 0.8 O2. Then, the Sb and Ir precursor metal salts are dispersed in the Sb 0.2 Sn 0.8 O2 particles, and then rapidly heated to 450°C to form Sb 0.3 Ir 0.7 O x @TB-IrO x / Sb 0.2 Sn 0.8O2. Rapid heating and pyrolysis are key factors in preparing nanocatalysts rich in twin boundaries. A large number of atomic nuclei are obtained by rapidly heating the precursor, and unconventional nuclei grow through particle collision and agglomeration, and then a large number of TBs are formed, resulting in dislocations and stacking at the contact interface of the nanocrystals. In Example 1, due to the rapid heating and pyrolysis preparation method, Sb 0.3 Ir 0.7 O x @TB-IrO x Nanoparticles in Sb 0.2 Sn 0.8 A large number of twin boundaries are formed on O2, resulting in dislocations and stacking at the contact interfaces of nanocrystals.
[0072] Figure 1 (b)-(e) are transmission electron microscope images and EDS element distribution images of the samples prepared in Example 1. It can be seen from the figure that Sb 0.3 Ir 0.7 O x @TB-IrO x The nanoparticles are evenly distributed on the carrier. The loaded nanoparticles have high crystallinity, abundant twin boundaries, and lattice fringe spacing. ( Figure 1 d) in Figure 5 can be attributed to the (111) crystal plane of IrO2.
[0073] Figure 2 The transmission electron microscope image and EDS element distribution diagram of comparative example 2 are similar to those of example 1. It can be seen that TB-IrO x Evenly distributed in Sb 0.2 Sn 0.8 O2 carrier, and has high crystallinity and twin boundaries, lattice fringe spacing This can be attributed to the (111) crystal plane of IrO2.
[0074] Figure 3 The X-ray diffraction patterns of the samples prepared in Example 1, Comparative Example 2 and Comparative Example 3 are shown in the figure. All samples show a typical fcc structure, with five diffraction peaks at 28.29°, 34.67°, 40.60°, 54.19° and 66.43°, corresponding to the (110), (101), (111), (211) and (112) crystal planes of rutile IrO2 (JCPDS No.43-1019). In addition, compared with Comparative Example 2, the signal peak of Example 1 shifts to the right, further confirming that Sb is introduced into IrO2. x middle.
[0075] X-ray photoelectron spectroscopy (XPS) was used to study the chemical valence states of the catalysts. Figure 4The XPS high-resolution spectra of Ir 4f, Sn 3d, Sb 3d and O1s of the samples prepared in Example 1, Comparative Examples 1, 2 and 3 are shown in FIG. Figure 4 In (a), the three groups of double peaks of Comparative Example 3 are located at 61.2eV and 64.3eV, 61.8eV and 64.9eV, and 63.2eV and 66.1eV, respectively, which can be attributed to Ir <3+ , Ir 3+ and Ir 4+ The three sets of double peaks of Comparative Example 2 are located at 61.0eV and 64.3eV, 61.8eV and 65.2eV, and 63.2eV and 66.2eV, respectively. Compared with Comparative Example 3 and Comparative Example 2, the three sets of doublets of Example 1 are shifted to negative binding energies due to the introduction of Sb, which indicates that Ir in Example 1 has a lower valence state. Figure 4 (b) shows that compared with Comparative Example 1, the signal peak of Example 1 shifts to the negative direction, which indicates that Sb 0.3 Ir 0.7 O x @TB-IrO x Nanocatalytic particles and Sb 0.2 Sn 0.8 O2 carriers have strong interactions. Figure 4 As shown in (c) and (d), in Example 1, Sb 3d, Sn 3d and O1s are shifted. The above results show that part of O also participates in the charge transfer between Ir and Sn, Sb, and part of the electrons are transferred from Sb to Ir through O, resulting in charge redistribution between the elements.
[0076] The samples prepared in the above-mentioned Example 1, Comparative Examples 1-3 and commercial IrO2 (C-IrO2) were used as catalysts to carry out electrocatalytic OER performance testing in a three-electrode system.
[0077] The electrochemical performance test was carried out by an electrochemical workstation, and 0.5M H2SO4 acidic solution was used as the electrolyte. 0.6 mg of the samples prepared in Example 1 and Comparative Examples 1-3 and C-IrO2 were placed in 1 mL of a solution of equal volumes of ethanol and water, and 100 μL of 5 wt% Nafion solution was added. The mixed solution was ultrasonicated for 1 h to ensure that the catalyst was evenly dispersed in the solution. 0.5 mL of the mixed solution was applied on a 1×2 cm carbon paper, and the applied area was 0.5 cm 2 The carbon paper coated with the catalyst was used as the working electrode. The Hg / Hg2SO4 electrode was used as the reference electrode and the platinum column electrode was used as the counter electrode to test the OER catalytic performance of the catalyst. Before using the three-electrode test, 50 mL of electrolyte was added to the electrolytic cell and purified with O2 for 30 minutes to reduce the error. Linear sweep voltammetry was used at 5 mV s -1All electrode potentials were iR compensated and converted to reversible hydrogen electrode (RHE) potentials according to the Nernst equation.
[0078] Figure 5 The electrochemical test diagrams of samples prepared from Example 1, Comparative Examples 1-3 and commercial IrO2 are shown in FIG. Figure 5 As shown in the LSV diagram of the polarization curve in (a), the OER catalyst performance is as follows: Example 1> Comparative Example 1> Comparative Example 2> Comparative Example 3> C-IrO2. At 10 mA cm -2 At the current density of 100 mA cm, the overpotential of Example 1 is 198 mV. -2 At the current density, compared with Comparative Example 1 (270 mV), Example 1 has a lower overpotential (249 mV), which proves that the supported catalyst has a relatively lower reaction energy barrier. Figure 5 From the Tafel calculation in (b), it can be seen that Example 1 has the smallest Tafel slope of 59.4 mVdec -1 , indicating that the reaction rate of this catalyst is the fastest among the prepared samples. At the same time, the electrochemical double layer capacitance (C dl ) was used to evaluate the number of surface active sites (ECSA) of samples prepared in Example 1 and other examples. Figure 5 (c) shows that C of Example 1 dl Value (188.5mF cm -2 ) is higher than that of comparative example 1 (170.18 mF cm -2 ), indicating that it has a larger electrochemical active area.
[0079] In addition, in order to reveal the reaction impedance between the solution and the electrode, the equivalent circuit diagram of the electrochemical impedance spectroscopy was fitted with the Nyquist plot. Figure 5 (d) in Figure 1 shows that the charge transfer resistance (Rct) of Example 1 is less than that of Comparative Example 1 and Comparative Example 2, which means that Example 1 has a smaller interfacial charge transfer resistance than other nanocatalysts. These results further confirm that the interaction between the support and the catalytic particles regulates the intrinsic catalytic activity of the nanocatalyst and effectively reduces the interfacial charge transfer resistance of the nanocatalyst. In addition, the stability of the catalyst to OER is an important parameter for evaluating the anode potential and corrosive electrolyte. Figure 5 (f) in 0.5M H2SO4, compared with Comparative Example 1 (10mV), Example 1 has a potential increase of only 3mV at 10mA cm -2 The results show that Example 1 has excellent stability. In addition, the mass activity of all synthesized catalysts was calculated at an overpotential of 270 mV, where Example 1 showed 4068 mA mg Ir-1 The highest mass activity is 33.62, 10.85, 7.369 and 1.28 times that of C-IrO2, Comparative Example 3, Comparative Example 2 and Comparative Example 1 ( Figure 5 e), which confirms that good dispersion enhances the OER activity of the catalyst. These results clearly indicate that the prepared catalyst is successfully loaded onto the Sb 0.2 Sn 0.8 On O2, good dispersion is conducive to exposing the active sites of the electrocatalyst. The performance of the nanocatalyst in Example 1 is better than most of the supported nanocatalysts reported previously.
[0080] Density functional theory (DFT) calculations were performed based on experimental data to investigate the mechanism of the excellent OER performance of Example 1, such as Figure 6 As shown. Through strain and doping effects IrO x The energy of the catalytic intermediates can be adjusted to enhance the electrocatalytic performance. x The (110) crystal plane is used to construct the model, and the ΔG *O -ΔG *OOH The free energy of is higher than the voltage of water electrolysis, and the free energy exceeds that of other steps, which indicates that the rate-limiting step of the oxygen evolution reaction is the nucleophilic attack of water on the surface oxygen. Figure 6 The density of states (DOS) diagram in (a) shows that IrO x After the introduction of Sb, the Ir 5d band center (ε d ) from -2.01eV(IrO x ) moves to −1.84 eV (Comparative Example 1), which reveals that the doping effect affects the electronic structure of the active sites.
[0081] Figure 7-12 In the experiment, the tension change was applied to the comparative example 1, and the change of its overpotential was calculated and the density of states was plotted. 0.3 Ir 0.7 O x @TB-IrO x -2% overpotential is the lowest. Fig.11 and Fig.12 The density of states shows that compared with the unstrained Sb 0.3 Ir 0.7 O x @IrO x , Sb 0.3 Ir 0.7 O x @TB-IrO x -2% epsilon dcloser to the Fermi level, indicating that the strain effect modulates the electronic structure to enhance oxygen adsorption, which can also be explained by the interaction with IrO x and TB-IrO x By plotting the relationship between the d-band center and the overpotential, the optimization effect of doping effect and strain on the adsorption capacity of catalysts with oxygen intermediates can be further confirmed. The volcano relationship between the d-band center and the overpotential ( Figure 6 b) in the figure indicates that Sb 0.3 Ir 0.7 O x @TB-IrO x -2% is at the lowest point of the volcano, and this catalyst has the lowest overpotential (0.502eV). Figure 6 In (c), ΔG in the catalyst *OOH -ΔG *OH There is also a "volcano" relationship between the overpotential, revealing that doping and stress on the metal oxide surface can improve the performance of the catalyst. The above DFT calculation results not only confirm that the synergistic effect between strain and doping on the carrier can adjust the electronic structure of the catalyst particles, but also confirm that the metal oxide carrier also has a regulatory effect on the electronic regulation of the catalyst particles, optimizing the adsorption energy between the catalyst active site and the oxygen intermediate, and significantly improving the acidic OER catalytic performance.
[0082] In order to further evaluate the catalytic activity of Example 1, it was sprayed on the treated Nafion 117 membrane and used as an anode catalyst in a PEM electrolyzer to electrolyze water ( Fig.13 a), where the catalyst loading is 0.33 mg cm -2 , containing 0.13 mg of Ir. The catalyst polarization curve at 80 °C ( Fig.13 b) shows that the activity of the catalyst in Example 1 is comparable to that of the catalyst in Comparative Example 1 with the same loading amount. -2 When the current density reaches 1.5A cm -2 and 2A cm -2 When , the voltage reaches 1.935 V and 1.997 V respectively. The above results show that the sample prepared in Example 1 has better performance as an anode material for a PEM electrolyzer than some other reported catalysts (Table 1).
[0083] Under the condition that all metal atoms are active for OER, the TOF values of the anode catalysts of Example 1 and Comparative Example 2 in the PEM electrolyzer are presented in Table 2. Among them, the nanocatalyst of Example 1 has a TOF of 2Acm -2 The turnover frequency (TOF) can reach 4.59O2s-1 Under the condition that only the metal atoms on the particle surface are active for OER, the TOF value of the anode catalyst of Example 1 is 21.65O2 s -1 (Table 3) At the same time, the comparative example 2 and the example 1 were tested at 2A cm -2 The electrolysis efficiency of PEM at the current density was 54.4% and 61.6% respectively (Table 4 and Fig.13 c). Compared with the electrolysis efficiency of the catalyst of comparative example 1 (59.7%), Example 1 has a higher electrolysis efficiency (61.6%) while reducing the amount of Ir used. In order to investigate the stability of the catalyst under commercial conditions, the sample prepared in Example 1 was used as the anode side catalyst. The PEM electrolyzer can be operated at 2A cm -2 200 hours of operation without significant performance degradation ( Fig.13 d). The initial increase in voltage is caused by the formation of bubbles between the catalysts due to the large specific surface area of the carrier. The subsequent fluctuations in voltage are due to the indirect accumulation and concentrated discharge of oxygen generated during the electrolysis process, which leads to changes in the active area of the catalyst, and then the overall performance is enhanced or reduced.
[0084] Table 1 Comparison of the performance of the samples prepared in Example 1 as anode materials for PEM electrolyzers with reported representative OER catalysts
[0085]
[0086] Table 2 TOF values of anode catalysts of Example 1 and Comparative Example 2 in PEM electrolyzer under the condition that all metal atoms are active for OER
[0087]
[0088] Table 3 TOF values of anode catalysts of Example 1 and Comparative Example 2 in a PEM electrolyzer under the condition that only metal atoms on the particle surface are active for OER
[0089]
[0090] *The estimated value of 21.2% surface atoms assumes a spherical nanoparticle with a diameter of 50nm and a single atomic unit cell with an atomic radius of 200pm. The unit cell cross-sectional area is 0.126nm 2 ; The surface area of a sphere with a diameter of 50 nm is 7850 nm 2 ; The number of atoms on the surface is 62301 atoms; The volume of a 50nm sphere is 65416.7nm 3 TB-IrO x The density is 11.15g / cm 3TB-IrO x The mass of a 5 nm sphere is 5.8×10 -18 g,Sb 0.2 Sn 0.8 The mass of a 50 nm sphere of O2 is 4.6×10 -14 g; therefore, the percentage of Ir, Sb, Tm and O atoms on the surface is 21.2%.
[0091] Table 4 Anode catalysts of Example 1 and Comparative Example 2 at 2A cm -2 Electrolysis power and efficiency in PEM electrolyzers at different current densities
[0092]
[0093] In order to further demonstrate the stability of the catalyst after continuous operation, the catalyst of Example 1 was characterized after the OER reaction ( Figure 14-16 ). Fig.14 The transmission image and Fig.15 XRD showed that after 200 hours of OER reaction, the appearance structure of the nanocatalyst in Example 1 did not change significantly and still had a large number of twin boundaries. Fig.16 XPS characterization showed that the Ir <4+ , Ir >4+ and Ir 4+ The signal peak of the valence state has no obvious shift, indicating that the valence state of Ir in the nanocatalyst of Example 1 has strong stability after the stability test.
[0094] Finally, it should be noted that the above-mentioned embodiments of the present invention are merely examples for clearly illustrating the present invention and are not limited to the above-mentioned specific implementation modes. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, which does not affect the essential content of the present invention. The parts of the technical scope of the present invention that are not exhausted by the embodiments herein are also within the scope of the present invention. All equivalent changes and modifications made according to the scope of the present invention shall fall within the scope of the present invention.
Claims
1. A method for preparing an antimony-doped iridium oxide catalyst, characterized in that: The following steps are involved: (1) Synthesis of Sb-doped SnO2 carrier powder: SnCl2·2H2O, citric acid and SbCl3 are dissolved in ethanol solution, then heated in a water bath and the pH of the mixed solution is adjusted to 5-7; then evaporated to obtain a white powder, which is then calcined in a muffle furnace, and then the obtained powder is washed, filtered and dried to obtain a blue powder, i.e., Sb 0.2 Sn 0.8 O2; (2) Synthesis of Sb m Ir 1-m O x @TB-IrO x / Sb 0.2 Sn 0.8 O2 nanocatalyst precursor: First, Sb 0.2 Sn 0.8 O2 and IrCl3 powders are placed in ethanol and ultrasonicated; then citric acid and SbCl3 are added and ultrasonicated again. Finally, the pH of the solution is adjusted to neutral; the resulting solution is dried into powder, and the precursor preparation is completed; (3) placing the precursor in a muffle furnace and calcining to obtain a black powder; washing the black powder several times to obtain Sb m Ir 1-m O x @TB-IrO x / Sb 0.2 Sn 0.8 O2 nanocatalyst, that is, antimony-doped iridium oxide catalyst.
2. The preparation method according to claim 1, characterized in that: In the step (1), the molar ratio of citric acid to metal salt is 0.5-1.5:5-15; the metal salt is SbCl3 and SnCl2·2H2O, wherein the molar ratio of SbCl3 to SnCl2·2H2O is 1-4:6-9.
3. The preparation method according to claim 1, characterized in that: The water bath heating time is 20-40 minutes, and the water bath heating temperature is 50-70°C; In step (1), the steps of washing, centrifuging and filtering the obtained powder are repeated 7 to 8 times; In the step (2), the two ultrasonic times are 0.5-1 hour and 1-2 hours respectively.
4. The preparation method according to claim 1, characterized in that: In the step (1), the pH of the mixed solution is adjusted by using a NaOH ethanol solution; the concentration of the NaOH ethanol solution is 1 mmol / mL.
5. The preparation method according to claim 1, characterized in that: In the step (1), the muffle furnace calcination condition is to heat to 500-600°C at 5°C / min, continue heating for 1-2 hours, and then naturally cool to room temperature.
6. The preparation method according to claim 1, characterized in that: In the step (2), Sb 0.2 Sn 0.8 The molar ratio of O2, citric acid and metal salt is 0.5-1:0.5-1.5:5-15; the metal salt is SbCl3 and IrCl3, wherein the molar ratio of SbCl3 and IrCl3 is 0-4:6-10.
7. The preparation method according to claim 1, characterized in that: In the step (1) and the step (2), the drying temperature is 40-60°C.
8. The preparation method according to claim 1, characterized in that: In the step (3), the muffle furnace calcination condition is to heat to 450-500°C at 10°C / min; the sample is heated continuously for 0.5-1 hour and then cooled naturally.
9. Sb prepared by the preparation method according to any one of claims 1 to 8 m Ir 1-m O x @TB-IrO x / Sb 0.2 Sn 0.8 O2 nanocatalyst.
10. The Sb according to claim 9 m Ir 1-m O x @TB-IrO x / Sb 0.2 Sn 0.8 Application of O2 nanocatalysts in acidic oxygen evolution reaction.